Photosynthesis and photoprotection in symbiotic corals - Maxim Y. Gorbunov; Zbigniew S. Kolber; Michael P. Lesser; Paul G. Falkowski (Limnology and Oceanography, 2001)
In zooxanthellate corals, excess excitation energy can be dissipated as heat (nonphotochemical quenching), thereby providing protection against oxidative damage by supraoptimal light in shallow reefs. To identify and quantify the photoprotective mechanisms, we studied the diel variability of chlorophyll fluorescence yields and photosynthetic parameters in situ in corals, using moored and SCUBA‐based fast‐repetition‐rate fluorometers. The results reveal that nonphotochemical quenching is triggered prior to saturation of photosynthetic electron transport by down‐regulation of the reaction centers of Photosystem II (PSII). This process dissipates up to 80% of the excitation energy. On a sunny day in shallow waters, the daily integrated flux of photons absorbed, and subsequently dissipated as heat, is ~4 times that used for photosynthesis. Fluorescence quenching is further accompanied by a slight reduction in the functional absorption cross section for PSII that results from thermal dissipation of excitation energy in the light‐harvesting antennae. These two processes are highly dynamic and adjust to irradiance changes on timescales consistent with the passage of clouds across the sky. Under supraoptimal irradiance, however, up to 30% of PSII reaction centers become photoinhibited, and these are repaired only after several hours of low irradiance. In shallow corals, between 10% and 20% of the reactions centers are chronically photoinhibited and appear to remain permanently nonfunctional throughout the year. Our results establish, for the first time, the suite of biophysical mechanisms that optimize photosynthesis while simultaneously providing photoprotection in symbiotic corals in situ.

The effects of UV radiation in the marine environment - Michael P. Lesser (Limnology and Oceanography, 2001)